A Kantian account of mathematical modelling and the rationality of scientific theory change: The role of the equivalence principle in the development of general relativity - Everett, Jonathan (Studies in history and philosophy of science. Part A, 2018)
•The role of the equivalence principle in the development of general relativity.•Identification of the role of conceptual analysis in this process.•Discussion of Cassirer's account of the rationality of scientific theory change.•Bolstering Cassirer's account through emphasising conceptual analysis.